ADAMTS5 in Osteoarthritis: Biological Functions, Regulatory Network, and Potential Targeting Therapies - Jiang, Lejian; Lin, Jiachen; Zhao, Sen; Wu, Jiaqian; Jin, Yongming; Yu, Li; Wu, Nan; Wu, Zhihong; Wang, Yue; Lin, Mao (Frontiers in Molecular Biosciences, 2021)
ADAMTS5 involves in the pathogenesis of OA. As the major aggrecanase degrading articular cartilage matrix, ADAMTS5 has been regarded as a potential target for OA treatment. We here provide an updated insight on the regulation of ADAMTS5 and newly discovered therapeutic strategies for OA. Pathophysiological and molecular mechanisms underlying articular inflammation and mechanotransduction, as well as chondrocyte hypertrophy were discussed, and the role of ADAMTS5 in each biological process was reviewed, respectively. Senescence, heredity, inflammation and mechanical stress are involved in the over-activation of ADAMTS5, contributing to the pathogenesis of OA. Multiple molecular signaling pathways were observed to modulate ADAMTS5 expression, namely, Runx2, YAP/TAZ, Notch, Wnt, NF-κB and the other inflammatory signaling pathways. However, the molecular regulatory network has not yet been elucidated, and the spatio-temporal expression pattern of ADAMTS5 remains unclarified. Based on the fundamental understanding of ADAMTS5 in OA pathogenesis, monoclonal antibodies and small molecule inhibitors against ADAMTS5 were developed and proved beneficial both in vitro and in vivo. Recent novel RNA therapies demonstrated significant suppressive effect on ADAMTS5 with high specificity in OA animal models. To sum up, ADAMTS5 inhibition and its signaling pathway-based RNA therapies showed great potential in future therapeutic strategies for OA.